Understanding Food Literacy Through Google Fit Application : A Case Study in Reframing Positive Communication - Alfira Isya Nabila; Thereza Angie Griffin; Rita Hartati (Concept: Journal of Social Humanities and Education, 2024)
In the digital era, food literacy—an essential competency for making informed dietary choices—has gained significance in enhancing not only individual health but also communication skills. This study investigates the role of the Google Fit application in improving food literacy and its subsequent impact on positive communication among university students. Utilizing a qualitative case study approach, we explored how the use of Google Fit influenced the understanding of food literacy and fostered supportive, constructive interactions among 20 English Literature students at UNIMED. Findings reveal that Google Fit’s features, such as calorie tracking and activity monitoring, significantly enhance students' awareness of nutrition and healthy eating behaviors. Furthermore, improved food literacy encouraged participants to engage in data-driven, empathetic dialogues, thus fostering positive communication. The results highlight the potential of mobile applications to serve as effective educational tools, not only for promoting health literacy but also for cultivating essential interpersonal skills. These findings underscore the importance of integrating digital tools into academic practices to bridge the gap between personal health education and broader social competencies.